Negative regulation of early B lymphopoiesis by interleukin 3 and interleukin 1 alpha. - Hirayama, F (1994)
We recently developed a two-step methyl cellulose culture system for murine lymphohemopoietic progenitors that are capable of differentiation along the myeloid and B-lymphoid lineages. In this system, two-factor combinations, which include steel factor plus interleukin (IL) 6, IL-11, or granulocyte colony-stimulating factor effectively supported the lymphomyeloid potential of primary colonies. Interestingly, IL-3 could neither replace nor act synergistically with steel factor in maintaining the B-lymphoid potential of the primary colonies although the frequency of colony formation was the same with IL-3 and steel factor. We now report that addition of IL-3 or IL-1 alpha to a permissive system suppresses the B-lymphoid potential of primitive progenitor cells in primary culture in dose-dependent fashion. In vivo transfer of the primary colonies to scid mice confirmed the suppressive effects of IL-3 and IL-1 alpha. In addition, IL-1 alpha inhibited pre-B-cell colony formation in the secondary culture. Once pre-B-cell colonies had formed in secondary culture, neither factor affected the proliferation of the pre-B cells. These results suggest negative regulatory roles for IL-3 and IL-1 alpha in early stages of B lymphopoiesis.